2021
DOI: 10.1007/s40123-021-00439-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Axial Length and IOL Power Based on Alternative A-Scan or Fellow-Eye Biometry in Macula-Off Rhegmatogenous Retinal Detachment Eyes

Abstract: Introduction: This study was performed to observe the potential refractive prediction error based on alternative A-scan ultrasound and fellow-eye biometry for phacovitrectomy in macula-off rhegmatogenous retinal detachment (RRD) eyes. Methods: Phakic macula-off RRD eyes without axial length (AL) measurements obtained using IOLMaster were included. Vitrectomy without lens extraction was performed for RRD repair.Preoperative AL was measured using alternative A-scan ultrasound (AL-US). Postoperative AL was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…It has been reported that a combined approach may lead to a slight myopic shift when the optical biometry is reliable. A comparable slight postoperative myopic shift has been reported in cases that underwent phacovitrectomy based on fellow-eye biometry 9 , 10 . That point was taken in consideration in the choice of the refraction power of the IOL of our patients, incorporating our own previous experience regarding refractive outcomes after phacovitrectomy.…”
Section: Discussionsupporting
confidence: 70%
“…It has been reported that a combined approach may lead to a slight myopic shift when the optical biometry is reliable. A comparable slight postoperative myopic shift has been reported in cases that underwent phacovitrectomy based on fellow-eye biometry 9 , 10 . That point was taken in consideration in the choice of the refraction power of the IOL of our patients, incorporating our own previous experience regarding refractive outcomes after phacovitrectomy.…”
Section: Discussionsupporting
confidence: 70%